2021
DOI: 10.3390/jcm10194486
|View full text |Cite
|
Sign up to set email alerts
|

A Network Analysis of Drug Combinations Associated with Acute Generalized Exanthematous Pustulosis (AGEP)

Abstract: Acute generalized exanthematous pustulosis (AGEP) is a rare skin adverse drug reaction. The pathophysiology and causative drugs associated with AGEP are poorly understood, with the majority of studies in AGEP focusing on a single-drug-outcome association. We therefore aimed to explore and characterize frequently reported drug combinations associated with AGEP using the WHO pharmacovigilance database VigiBase. In this explorative cross-sectional study of a pharmacovigilance database using a data-driven approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The patient demographics in this case series are generally comparable to other observational studies. Indeed, the higher frequency of women patients in our study is in line with the existing evidence [7,11,265,266], and there is agreement on the lower age observed among men in comparison to women patients [266]. However, we note that the overall mean age in our case series (48.6 years [SD 21.6]) was slightly lower than the 51.7-62 years mean age reported in other observational and multi-center studies [7,8,10,12], as well as the 57.3 years reported in a recent pharmacovigilance study including 2649 case reports from the World Health Organization pharmacovigilance database (WHO-VigiBase) [266].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The patient demographics in this case series are generally comparable to other observational studies. Indeed, the higher frequency of women patients in our study is in line with the existing evidence [7,11,265,266], and there is agreement on the lower age observed among men in comparison to women patients [266]. However, we note that the overall mean age in our case series (48.6 years [SD 21.6]) was slightly lower than the 51.7-62 years mean age reported in other observational and multi-center studies [7,8,10,12], as well as the 57.3 years reported in a recent pharmacovigilance study including 2649 case reports from the World Health Organization pharmacovigilance database (WHO-VigiBase) [266].…”
Section: Discussionsupporting
confidence: 93%
“…Antibiotics are often the most prevalent drugs associated with AGEP onset [7][8][9][10][11][12][13][14]265,268,269], accounting for 17 out of the 26 (61.4%) AGEP cases studied by Barbaud et al [8], 26 of the 58 (44.8%) AGEP cases studied by Hotz et al [265], and 14 (66.7%) out of the 21 AGEP patients studied by Choon et al [11]. Additionally, the beta-lactam antibacterial amoxicillin was the most reported drug (21.6%) in the study of 2649 AGEP individual case safety reports (ICSRs) with at least two reported drugs in the World Health Organization (WHO) pharmacovigilance database (WHO VigiBase) [266]. In the multinational EuroSCAR case-control study, which included 97 validated AGEP cases, antibiotics, such as pristinamycin, aminopenicillins, and quinolones, were suspect drugs in 10%, 19%, and 9% of the AGEP patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEC in signal detection) reduces the chances of having a real connection between the investigated drug-adverse event pair. Previous publications in the ICSR network analysis field were mainly focused on descriptive analysis of spontaneous reporting databases [18,19,30], while other studies provided support for case review during signal evaluation by network visualization [23,29], or described certain adverse events [21,22]. Furthermore, two recent studies applied network metrics for signal detection purposes [24,25], but the approach was different from NEWS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were published in relation to the development of improved statistical signal detection methodologies that showed promising results, such as vigiRank [11], combination of supervised learning and Bradford Hill's causality considerations [12], application of machine learning [13], false discovery rate detection [14,15], competition bias removal [16], and co-prescription bias and associated unmasking [17], but currently these methods are not used widely by regulatory bodies or pharmaceutical companies. In recent years, the field of network theory and analysis was researched extensively, and various methods were applied on spontaneous reporting databases in order to describe the network characteristics of spontaneous adverse event report databases [18][19][20], certain adverse events [21,22] and support decision rules [23]. Network analysis as a part of signal detection methods has also been published recently, for co-reported community detection [24] and adverse event severity estimation and risk profiling [25].…”
Section: Introductionmentioning
confidence: 99%